Public Criminology: Reimagining Public Education and Research Practice - Deborah Jones (Springer Nature Switzerland, 2023)
This book discusses the role and impact of ‘Public Criminology’. It brings together a collection of key scholars who have been at the fore of empirical and practice work in relation to understanding how ‘Public Criminology’ can engender academic activism. Split into two parts, it focusses on academic activism and research methodologies, and public criminology and pedagogical practice. It includes chapters on a range of topics including Inside-Out teaching, it discusses the role of social scientists and stepping outside of established research practices, and how students, the public and children can be engaged in criminological learning and issues to become agents of social change. It includes a reflection on how ‘Public Criminology’ has developed both in the UK and USA. It speaks to students, researchers and academics alike involved in teaching and learning within the discipline of Criminology and those who wish to evaluate practice and ensure their interventions have impact on commissioners and policymakers.